Design of shunt hybrid active power filter (SHAPF) to reduce harmonics in AC side due to Non-linear loads - Madhu B R; Dinesh MN; Ravitheja BM (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The quality of power is a major concern because of harmonics in the lines due to various sources. Passive filters have been used to eliminate the specific harmonics. In this paper shunt hybrid active power filter which consists of shunt active filter and shunt passive filter is designed to reduce harmonics in source   side for non linear loads. The shunt passive filter includes a tuned RLC circuit that behaves like a band-pass filter for a particular harmonic content. The shunt active filter is a VSI that produces reverse harmonic current based on Clarke’s transformation. This paper presents the control strategy by implementing instantaneous reactive power theory to design Shunt Hybrid Active Filter (SHAPF) for a non linear load. The proposed control technique is simulated using MATLAB SIMULINK, Results prove there is considerable reduction in THD of source current from 30.35% to 3.25% with the proposed controller on   shunt hybrid active power filter.   The performance of SHAPF is better than Passive and Shunt Active Power Filters.